2018
DOI: 10.1155/2018/4305408
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis-4 Model Influences Results of Patients with Hepatocellular Carcinoma Undergoing Hepatectomy

Abstract: Background Several noninvasive models based on routine laboratory index have been developed to predict liver fibrosis. Our aim is to discuss whether these indexes could predict prognosis in patients with hepatocellular carcinoma undergoing hepatectomy. Methods This study retrospectively enrolled 788 consecutive hepatocellular carcinoma patients undergoing liver resection in the cohort. Univariate and multivariate analysis were used to identify the risk factors of complications, survival, and disease-free survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The degree of liver fibrosis can be estimated using the fibrosis-4 (FIB-4) index, which takes into account the patient's age, AST, ALT, and platelet count [162] . Several studies have demonstrated that higher FIB-4 score is associated with worse outcomes, including increased risk of developing HCC in setting of chronic HCV infection and increased persistence of HCC post-hepatectomy [163][164][165] . Fibrosis evidently influences clinical outcomes in HCC.…”
Section: Formation Of a Physical Barriermentioning
confidence: 99%
“…The degree of liver fibrosis can be estimated using the fibrosis-4 (FIB-4) index, which takes into account the patient's age, AST, ALT, and platelet count [162] . Several studies have demonstrated that higher FIB-4 score is associated with worse outcomes, including increased risk of developing HCC in setting of chronic HCV infection and increased persistence of HCC post-hepatectomy [163][164][165] . Fibrosis evidently influences clinical outcomes in HCC.…”
Section: Formation Of a Physical Barriermentioning
confidence: 99%
“…Over the years, several studies have validated its role as a marker of hepatic fibrosis [18,19] . An important study [20] indicated that the Fib-4 index not only demonstrated the best predictive ability for cirrhosis, but it was also an independent prognostic factor for postoperative hepatic insufficiency, overall survival, and disease-free survival for HCC patients with radical liver resection. They also stratified patients, with the cut-off value of 3.15, into Low and High fibrosis-4 groups.…”
Section: Fib-4mentioning
confidence: 99%